Implementasi Digital Learning pada Materi Tekanan Zat untuk Peserta Didik Kelas VIII SMP - Mahardika, Sekar Putri; Ayatillah, Arini Maila; Mardhatilla, Wilda; Mahdiannur, Muhamad Arif; Subekti, Hasan (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2023)
Students sometimes feel bored with the lecture-based learning model, so as educators it is necessary to try to apply digital learning in the classroom. Digital learning is expected to increase students' interest and motivation in learning so that students feel comfortable and the knowledge they gain will be easy for them to accept. This study aims to analyze the use of digital learning media on students' interest and motivation to learn. The research method used in this research is a survey using interest and motivation questionnaires. The survey results from the aspect of student interest indicate that on average each indicator of the use of digital learning can help increase student interest in learning, while the motivational aspect shows that on average each indicator of the use of digital learning can help increase students' learning motivation. The results of this survey indicate that digital learning is useful so that it can increase interest and motivation to learn in students.